Selective oxidation of glycerol to mesoxalic acid by laccase/2,2,6,6-tetramethylpiperidine-N-oxyl system : effect of process conditions and the kinetic modeling - Hong, Chi Shein; Chin, S. Y.; Cheng, C. K.; Chua, Gek Kee (Taylor & Francis, 2019)
A pharmaceutical importance compound, mesoxalic acid, can be produced through selective oxidation of glycerol using laccase/2,2,6,6-tetramethylpiperidine-N-oxyl system. Since mesoxalic acid is the fourth product in the serial oxidation, identification of the reaction conditions and its’ kinetic to maximize the production is essential. Hence, the objective of this study is to examine the effects of process conditions on the distribution of the products and the kinetic. Mesoxalic acid attained was 0.0712 M (>200% of control) at 19 °C, pH 5.5, 1:3 of glycerol/TEMPO ratio and TEMPO/laccase ratio of 9:3. To conclude, a moderate temperature that preserves the activity of laccase would favor the formation of mesoxalic acid. The serial chemical reactions could be expressed by a power law rate obtained via MATLAB through fitting of the experimental kinetic data. Oxidising from tartronic acid to mesoxalic acid was found to require higher activation energy (25.06 kJ/mol) as compared to other steps.